Numerıcal study of jet ımpıngement coolıng on a flat plate - Kaddafi, Mohamed Saleh (My University, 2017)
Jetler, özellikle yüksek ısı transfer katsayısına ulaşmanın en iyi yöntemlerinden biridir ve bu nedenle birçok mühendislik uygulamasında kullanılır.

Impinging jets are one of the best methods of achieving particularly high heat transfer coefficient and are therefore employed in many engineering applications. In this study, we seek to understand the mechanism of the distributed heat on the flat plate with the goal of identifying preferred methods to predicting jet performance
Keywords: Isı transfer katsayısı; Jetler; jetler jets; Makine, Mühendislik; Soğutma; Soğutma teknikleri